The personality of the criminal as an element of the forensic characteristics of collaborative crimes - Perepelytsia, S. I. (Аналітично-порівняльне правознавство, 2025)
The purpose of the study is to determine the place of the personality of the criminal in the system of elements of the forensic characteristics of criminal offenses related to collaborative activities, and to outline the general features of the collaborator. It is noted that the generalized concept of the criminal’s personality remains a certain abstraction until it is filled with specific content: social, demographic, psychological and moral characteristics. This is due to the fact that a comprehensive study of the criminal’s personality cannot be limited to the establishment of individual features that mostly superficially characterize the person. It must be carried out with the necessary depth of study of the features in their interaction, which guarantees a more complete identification of the factors of the genesis of the criminal’s personality. Considering that the system of characteristics of the offender’s personality contains demographic data, individual qualities and psychological characteristics, it has been established that this concept expresses the essence of the person who committed a criminal offense. The personality of the offender, as an element of forensic characteristics, is a set of essential and established social properties and signs and socially significant biopsychological features of an individual that, objectively realized in a collaborative crime, give the committed act the character of a public danger, and the perpetrator the property of a public danger, for which this person is held criminally liable in accordance with current legislation. It is indicated that the role and significance of providing a forensic characterization of a collaborator forms a new basis for the pluralism of forms and methods of conducting a pre-trial investigation of this type of criminal behavior. The socio-legal aspect of the relevant issues is substantiated, since today the issue related to the social essence of collaborative activity, its main substantive characteristics, which are closely intertwined and directly affect the functioning of the state as an entity initiated by society, remains important. It has been proven that in the context of repelling the armed aggression of the Russian Federation and the widespread use of our citizens by the occupying country, by involving them in collaborative activities, it is important to form an idea of a person-collaborator in order to develop basic forensic and criminal procedural algorithms and methods for investigating collaborative activities.